Bacterial SET domain proteins and their role in eukaryotic chromatin modification - Alvarez-Venegas, Raúl (Frontiers in Genetics, 2014)
It has been shown by many researchers that SET-domain containing proteins modify chromatin structure and, as expected, genes coding for SET-domain containing proteins have been found in all eukaryotic genomes sequenced to date. However, during the last years, a great number of bacterial genomes have been sequenced and an important number of putative genes involved in histone post-translational modifications (histone PTMs) have been identified in many bacterial genomes. Here, I aim at presenting an overview of SET domain genes that have been identified in numbers of bacterial genomes based on similarity to SET domains of eukaryotic histone methyltransferases. I will argue in favor of the hypothesis that SET domain genes found in extant bacteria are of bacterial origin. Then, I will focus on the available information on pathogen and symbiont SET-domain containing proteins and their targets in eukaryotic organisms, and how such histone methyltransferases allow a pathogen to inhibit transcriptional activation of host defense genes.